Antiphospholipid antibodies and pregnancy outcome of assisted reproductive treatment: A systematic review and meta‐analysis. (3rd June 2021) - Gao, Rui; Zeng, Rujun; Qing, Pingying; Meng, Cheng; Cheng, Kemin; Zhang, Sirui; Chen, Hanxiao; Jin, Xiaolei; Qin, Lang; Li, Tao
Abstract: Problem: Antiphospholipid antibodies (aPLs) are a group of autoantibodies associated with a variety of pregnancy complications, but the impact of aPL on the outcomes of assisted fertility treatment (ART) is controversial. This systematic review and meta‐analysis were designed to explore the association between aPL and ART outcomes and to explore in which stages does aPL play a role. Method of Study: PubMed and Cochrane database were systematically retrieved, and odds ratios (ORs) or risk ratios (RRs) with 95% confidence intervals (CIs) were calculated in a random‐effect model or fixed‐effect model according to the heterogenicity assessed by the Cochran Q and I 2  statistic test. Of 246 records identified by the search, 10 case‐control studies and 13 cohort studies that explored the association between aPL and in vitro fertilization (IVF) and/or intracytoplasmic sperm injection (ICSI) were analyzed. Results: The results showed that aPL positive rate was higher in females who failed in IVF/ICSI than those who succeeded in IVF/ICSI (OR: 3.62, 95% CI: 1.95–6.74). This study also indicated that females positive for aPL have a higher miscarriage rate (RR: 1.68, 95% CI: 1.24–2.28) than those negative for aPL, but live birth rate, biochemical pregnancy rate, and clinical pregnancy rate were similar between two groups (RR: 1.01, 95% CI: 0.91–1.12; RR: 1.18, 95% CI: 0.57–2.43 and RR: 0.95, 95% CI: 0.80–1.13). Conclusions: There was higher aPL prevalence in females with adverse IVF/ICSI outcomes. It seems that aPL mainly affects the miscarriage rate, but has little effect on live birth rate, biochemical pregnancy rate, and clinical pregnancy rate. Routine detection of aPL before IVF/ICSI treatment is meaningful.